2022
DOI: 10.3389/fphar.2022.920977
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Astragaloside IV on chronic intermittent hypoxia-induced vascular endothelial dysfunction through the calpain-1/SIRT1/AMPK signaling pathway

Abstract: Vascular endothelial dysfunction (VED) is linked with the pathogenesis of obstructive sleep apnea (OSA) comorbidities, such as cardiovascular disease. Astragaloside IV (As-IV) has exhibited significant improvement for endothelial dysfunction. Nonetheless, the protective mechanism is not clear. Therefore, the present study investigated the potential mechanism of As-IV on VED. Calpain-1 knockout and wild-type C57BL/6 mice exposed to chronic intermittent hypoxia (CIH) were established and treated with As-IV (40, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is important to observe that many molecules have only been tested in mouse models, such as Astragaloside IV, which showed an improvement of hypoxia-induced endothelial function [ 97 ]; Tauroursodeoxycholic acid, against hepatic damage induced by HI [ 98 ]; Pitavastatin, showing a reversal of IH-induced myocardial hypertrophy, cardiac function, perivascular fibrosis and inflammatory indices [ 99 ]; Allopurinol also showed beneficial effects in mouse models of OSAS with a reduction of lipid peroxidation and an improvement in cardiac function [ 100 ]; and for all molecules, clinical trials are needed.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to observe that many molecules have only been tested in mouse models, such as Astragaloside IV, which showed an improvement of hypoxia-induced endothelial function [ 97 ]; Tauroursodeoxycholic acid, against hepatic damage induced by HI [ 98 ]; Pitavastatin, showing a reversal of IH-induced myocardial hypertrophy, cardiac function, perivascular fibrosis and inflammatory indices [ 99 ]; Allopurinol also showed beneficial effects in mouse models of OSAS with a reduction of lipid peroxidation and an improvement in cardiac function [ 100 ]; and for all molecules, clinical trials are needed.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] Although few literature reports exist on Me2 in cerebral ischemia, it is associated with multiple molecular mechanisms of cerebral ischemic injury, so Me2 is also considered a potential target for future research. Researchers have found some signal pathways about AS-IV against cerebral ischemic injury, and AS-IV inhibited the occurrence of oxidative stress and mitochondrial dysfunction through the calpain-1/SIRT1/AMPK signal pathway; 39 AS-IV stimulates angiogenesis through the PI3K/Akt pathway. 40 These are similar to the molecular mechanisms of Me2 regulation.…”
Section: Food and Function Papermentioning
confidence: 99%
“…AMPK exists in the form of α, β, and γ, and is directly activated by interaction between Sestrin1 and Thr 172, which have been demonstrated in cardiomyocytes (Yuan et al, 2022). When activated, AMPK maintains cell energy balance, turning on the productive catabolic pathway while shutting down the energy-consuming synthetic pathway, which contributes to cell survival and cardiovascular system function when cells are hypoxic (Wu and Zou, 2020;Zhao et al, 2022). Studies have shown that normal energy metabolism of the myocardium is the material basis for maintaining the stability of cardiac internal environment and myocardial systolic function.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%